Compendium on key international & African children's rights instruments - Prepared by the Centre for Child Law, Faculty of Law, University of Pretoria (Pretoria University Law Press (PULP), 2018)
This booklet has been prepared by the Centre for Child Law, Faculty of Law, University of Pretoria. In 2018, the Centre for Child Law celebrates 20 Years of strategic litigation, research and advocacy in order to advance child law and children's rights in South Africa. The United Nations Convention on the Rights of the Child and the African Charter on the Rights and Welfare of the Child have played an important role in shaping children's rights jurisprudence in South Africa. This booklet is accompanied by a flash drive that contains a number of General Comments issued by the UN Committee on the Rights of the Child and the African Committee of Experts on the Rights and Welfare of the Child. This is an updatable resource - as the Committees produce future General Comments and issue views arising from their communications procedures, the new documents can be added to the flash drive, allowing this small compendium to grow as the jurisprudence expands.